Work-to-Family Spillover Effects of Workplace Negative Gossip: A Mediated Moderation Model - Liu, Tianyuan; Wu, Lin; Yang, Yang; Jia, Yu (Frontiers in Psychology, 2020)
Existing research has found that workplace negative gossip exerts a negative impact on employees and organizations. However, there is a lack of study on the spillover effect of workplace negative gossip on employees’ families. This paper aimed to address this gap in prior literature. Based on resource conservation theory, we chose married employees who perceived or suffered from workplace negative gossip as the subjects of our study and analyzed the effect of workplace negative gossip on their work-family conflict. We adopted a self-reported questionnaire to assess employees’ perception or experience of workplace negative gossip, psychological distress, level of neuroticism, and work-family conflicts. A total of 245 valid employee questionnaires were obtained from two-wave data collection in China. The results of empirical analysis showed that workplace negative gossip perceived or suffered by employees has a positive impact on their work family conflicts, and psychological distress plays a mediating role in the relationship between perceived or suffered workplace negative gossip and employees’ work-family conflict. Furthermore, we found that employees’ level of neuroticism moderates the positive effect of workplace negative gossip and work-family conflict, and it also moderates the meditating effect of workplace negative gossip on employees’ work-family conflict by psychological distress. The conclusion of this paper supported our previous hypotheses. Finally, according to the above findings, we discussed the theoretical contributions, practical significance, and limitations of the study and provided some practical suggestions for managers.